Rethinking the Green New Deal: Using climate policy to address inequality - Aparna Mathur (American Enterprise Institute (AEI), 2019)
The Green New Deal is an ambitious policy proposal that seeks a cleaner economy and a more equal and fair society. A well-designed carbon tax could be an effective method for financing such a proposal.
Keywords: A; 330; Green New Deal